THE IMPACT OF ECOLOGICAL FACTORS ON TOURISM DEVELOPMENT IN KVEMO KARTLI REGION (Globalization and Business, 2023)
In this Article we discuss environmental issues necessary for safe and sustainable development of tourism as an integral part of economic relations. We focus to examine the impact of anthropogenic effects on the environment, which manifests itself in organizing recreational utilization of nature.We refer here to the impact of ecological problems on human health in Kvemo Kartli region, which is very attractive tourist destination and has a great potential for tourism devel- opment as of its cultural and historic heritage.